Evaluation of the SVOne: A Handheld, Smartphone-Based Autorefractor. Issue 12 (December 2015) - Ciuffreda, Kenneth J.; Rosenfield, Mark
ABSTRACT: Purpose: The SVOne is a portable Hartmann-Shack wavefront aberrometer that can be attached to a smartphone to determine the refractive error of the eye objectively. The aim of the present study was to compare the findings of the SVOne with retinoscopy, subjective refraction, and two commercially available autorefractors (Topcon KR-1W and Righton Retinomax-3). Methods: Refractive error was assessed both with and without cycloplegia in 50 visually normal, young adults using the five techniques described above. Further, to assess repeatability of the instruments, the entire procedure was repeated in a subgroup of 10 subjects. All data were analyzed in terms of power vectors ( M, J 0, and J 45 ). Results: No significant difference was observed between the mean values of M (spherical equivalent) for the different techniques. However, a significantly higher mean value of precyclopegic J 0 was recorded for the SVOne, which also had the highest limits of agreement for both the J 0 and J 45 astigmatic components. Retinoscopy and subjective refraction showed the best repeatability (in terms of M values) for precycloplegic and postcycloplegic measurements, respectively. High and significant linear correlations were observed between the subjective findings and the other four techniques. Conclusions: The results indicate that the SVOne handheld aberrometer provides measurements of refractive error in normal, young individuals that are not significantly different from other subjective and objective procedures. This instrument is valuable for vision screenings, as well as examinations taking place outside the clinical office. It may also serve as an adjunct in the standard optometric examination.